Comparative Study on Seismic Analysis of Multi Storey RCC Building with Mass Irregularities Using NBC 105:2020 and IS 1893:2002 (International Journal of Innovative Research in Engineering & Management, 2022)
Today there is increasing population and  demand of housing is increasing day by day, because of  which multi storied buildings are constructed. These  buildings are vulnerable to earthquake because of non uniform distribution of loads as well as no uniform  stiffness in building. As the form of building depends upon  the requirements of the client the building may be  subjected to the mass irregularity as well as stiffness  irregularity. The building which have mass irregularity and  stiffness irregularity must be safe during earthquake  .Building should be able to withstand the earthquake force  and should perform better when earthquake hit that  building.In Nepal both IS code and NBC is use for  analyzing the building for its performance against  earthquake. Because of similar topography of India and  Nepal. Nepal allow the use of IS code as well as its own  code for the seismic analysis of structure. In Nepal new  code is implemented removing the defects of old NBC  1994. In Nepal now NBC 105:2020 is followed for  analysis of building .Nepal is located in earthquake prone  zone seismic performance of building must be done for the  design of any building within its territory. Hence, for the  optimum performance of building regarding seismic  performance, it has been seen that designers undertake the  design considering both IS Code and NBC code.  Here, we study the performance of building comparing  Nepal building code with that of IS 1893:2002. In this  paper, regular building G+7 with plan area 15mX15m is  taken for the analysis and beam and column size are taken  constant. The building is analyzed using ETABS 2016.  Comparison is made for the displacement,drift,store shear,  storey stiffness and base reaction.
Keywords: Base shear; Storey Shear; Seismic Analysis; Storey Drift